Vernonanthura nana (Asteraceae: Vernonieae), a new species from the Paraná State (Brazil) - Vega, Alvaro Jose; Dematteis, Massimiliano (Phytotaxa, 2016)
A new species of Vernonanthura (Asteraceae), V. nana, from the Brazilian state of Paraná is described and illustrated. The new species resembles V. squamulosa but differs in its geographical distribution, habitat, shape and pubescence of the leaves, and involucre length.